Advanced project management a complete guide to the key processes, models and techniques - Orr, Alan D.; Gale Group (London Kogan Page, 2004)
This handbook clearly explains the skills, processes, methods and tools that will enable a project manager to handle more complex projects.
Starting an advanced project successfully -- Building the macro plan -- Building the detailed project plan -- Building the project team -- How to run the project on a day-to-day basis -- Monitoring and controlling the project -- Successfully shutting down the project -- Emergency actions.
Electronic reproduction.
Keywords: Project management; Electronic books